EMOTION, AROUSAL AND SLEEP DISORDER - Chóliz Montañés, Mariano (Anales de Psicología / Annals of Psychology)
Several theoretical perspectives have been used to explain persistent insomnia. Of these, somatic, cognitive, and emotional arousal have been a great significance on the planning of behavior therapies for this disorder. The somatic arousal hypothesis assume that ionsomniacs have heightened physiological arousal and muscle tension that is antagonistic to sleep. Nevertheless, there has been little experimental support for the somatic arousal exclusively, and there is evidence that cognitive and emotional arousal plays an important role in etiology and maintenance of sleep difficulties. Active mind at bedtime, worrying, planning, difficulty controlling thoughts, anxiety, or depression may precipitate and maintain sleep disturbances.